Challenges for the cataract surgeon treating people with dementia: a qualitative study exploring anesthetic choices - Jefferis, Joanna Mary (Dove Medical Press, 2014)
BACKGROUND: In light of the growing number of people with dementia and age-related cataract, as well as changing anesthetic practices for cataract surgery, this study aimed to explore the experiences of cataract surgeons in managing patients with dementia and making anesthetic decisions. METHODS: This was a qualitative study using semistructured interviews with senior cataract surgeons from two centers in England. Fourteen surgeons were interviewed, and a thematic approach informed by grounded theory was used for the analysis. RESULTS: Choice of anesthesia for people with dementia was a central theme arising from the data. Surgeons varied in their thresholds for using general anesthesia. Decisions about suitability for local anesthesia were limited by time constraints and generally made rapidly and based on instinct; dementia was not always apparent at the point of preassessment. Surgeons used a variety of topical, sub-Tenon’s, and sharp needle blocks for people with dementia. Surgeons discussed techniques to help patients tolerate local anesthesia, such as clear communication, a primary nurse, hand-holding, and support from an anesthetist. However, within our sample, some surgeons had had negative experiences of operating on people with dementia, where an incorrect judgment had been made that they could tolerate local anesthetic cataract surgery. CONCLUSION: This study highlights the differing practices of cataract surgeons when making anesthetic choices for people with dementia and the challenges they face. In order to avoid the situation of a patient with dementia becoming distressed during awake surgery, increased time at preassessment and anesthetic support may be beneficial.